DIRECTIONS FOR IMPROVING THE EFFECTIVE MANAGEMENT OF THE DEVELOPMENT OF SMALL INDUSTRIAL ZONES - Shodmonkulov , Kamoliddin (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article analyzes the directions for improving the effective management of the development of small industrial zones. The study highlights the economic importance of small industrial zones, their role in regional development, and existing management challenges. It also substantiates key directions for their development, including strengthening the legal and institutional framework, modernizing infrastructure, improving the investment climate, introducing digital management systems, and expanding public-private partnerships. The results of the study contribute to increasing the efficiency of small industrial zones and ensuring regional economic growth.